Increased Production Of True Shallot Seed With Applications Of Paclobutrazol And Salicylic Acid On Drought Conditions - Nisrina Ayu Cahyani; Yaya Hasanah; Sarifuddin Sarifuddin (UNIVED Press, Dehasen University Bengkulu, 2022)
Onion red is wrong one commodity horticulture which includes plant vegetable and usually used for spice. Increase Request onion red cause needed cultivation plant onion red on condition stress drought for reach production highest . Study this aim for knowing type and dose as well as combination paclobutrazol and sour salicylate on condition stress drought for increase production onion red.Research this held on house glass in the garden test Faculty Agriculture University North Sumatra Muhammadiyah . design experiments that have used in study this is design random factorial group with 3 factors . Factor first level drought with 2 levels treatment ie : 80% capacity roomy and 40% capacity roomy . Factor second paclobutrazol with 4 levels treatment namely 0 mg/l, 15 mg/l, 30 mg/l, 45 mg/l. Factor third Sour salicylate with 3 levels namely 0 mg/l, 50 mg/l, 100 mg/l. Observation parameters observed _ is length plant , number leaf , weight Fresh Bulbs , Weight Bulbs Dry and Bulb Diameter. Results study show gift factor single paclobutrazol and factor single sour salicylate no increase growth and production onion red.. Giving paclobutrazol with level 45 mg/l at 80% capacity roomy have score long plant and amount leaf highest compared to 40% Capacity roomy . Giving sour salicylate on concentration 50 mg/l at condition 80% capacity roomy increase weight tubers fresh , tuber dry and tuber diameter . Interaction treatment paclobutrazole , acid salicylate and stress drought could increase growth and production on K1S1P3 combination.